2020
DOI: 10.1002/brb3.1956
|View full text |Cite
|
Sign up to set email alerts
|

Serum pentraxin 3 as a biomarker for prognosis of acute minor stroke due to large artery atherosclerosis

Abstract: Objectives Pentraxin 3 (PTX3) may reflect local inflammatory status in tissues and thus serve as a potential biomarker of inflammation. Here, we investigated the utility of serum PTX3 as an index for assessing the 90‐day prognosis of acute minor stroke patients. Materials & Methods Acute minor stroke patients ( N = 241) and matched healthy control subjects ( N = 241) were prospectively recruited. Clinical, laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In general, those results are well-supported by another research. APCS , the member of the Pentraxin family, is involved in amyloidosis but it is also known to exert anti-inflammatory and antifibrotic properties (in particular, to inhibit monocyte differentiation into proinflammatory macrophages), thus could be used as inflammation and large artery atherosclerosis biomarker [ 58 ]. Similarly, the transgelin, acting via the transgelin–actin complex and modulating the reorganisation of the actin cytoskeleton, is known to participate in the regulation of the blood flows of coronary arteries, and thus is a promising therapeutic target for the treatment of myocardial ischemia [ 59 ].…”
Section: The Role Of Hsps In Cvdsmentioning
confidence: 99%
“…In general, those results are well-supported by another research. APCS , the member of the Pentraxin family, is involved in amyloidosis but it is also known to exert anti-inflammatory and antifibrotic properties (in particular, to inhibit monocyte differentiation into proinflammatory macrophages), thus could be used as inflammation and large artery atherosclerosis biomarker [ 58 ]. Similarly, the transgelin, acting via the transgelin–actin complex and modulating the reorganisation of the actin cytoskeleton, is known to participate in the regulation of the blood flows of coronary arteries, and thus is a promising therapeutic target for the treatment of myocardial ischemia [ 59 ].…”
Section: The Role Of Hsps In Cvdsmentioning
confidence: 99%
“… 5 , 6 For instance, previous extensive numerous studies had documented that patients with a poor prognosis after stroke had a significant increase in inflammatory markers including pentraxin 3, interleukin-18 (IL-18), interleukin-6, interleukin-8, and high-sensitivity C-reactive protein (hs-CRP). 7–9 Many studies have shown that higher levels of inducible nitric oxide synthase (iNOS), systemic immune-inflammation index, macrophage inflammatory protein 1α (MIP-1α), and hs-CRP are positively associated with increased risk for PSD. 10–12 In another study, IL-18 has also been shown to be correlated with PSD and plays an important role in the development of depression-like behaviors through the IL-18 receptor/NKCC1 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…PTX3 has attracted interest in relation to vascular pathology and pregnancy complications [10][11][12][13][14][15]. Elevated levels of PTX3 have been suggested to predict cardiovascular events, independently of other risk factors, such as increased CRP.…”
mentioning
confidence: 99%